Implementasi Pendidikan Karakter Religius Melalui Kegiatan Mentoring Pada Siswa Kelas V SDIT MTA GEMOLONG - Jamila, Ima Nur; , Nur Amalia, S.S., M.Teach (2017)
In this era, Indonesian young generation situation is increasingly worrisome in terms of their behavior and achievement. Therefore appropriate steps are needed to address the poor condition of the children of this nation. One possible ways is through character education. The purpose of this study is to describe the form of a religious character education in SDIT MTA Gemolong, to describe the application of mentoring activities in SDIT MTA Gemolong, and describe the process of internalization of the religious character of the students in mentoring activities in SDIT MTA Gemolong. This study is a qualitative research design. The primary source of this research is the principal, homeroom teacher, and students. A secondary source in the form is official document from the school. Informant in this research is the principal, teachers, and students. The technique of collecting data through observation, interviews, and documentation. The validity of the data is using a triangulation of sources and techniques. Data analysis techniques are data reduction, data presentation, and conclusion. The results show that mentoring is effective activities in shaping the religious character of the students, mentoring activities are conducted by homeroom teacher every Monday to Friday for an hour, and mentoring contains memorizing activities of hadith and daily prayer that aims to help students achieve their targets. The internalization process of religious values in the mentoring is to provide advice, motivation, role model, and repeated adminition repeatedly to the student so that it can be internalized students practice in daily life. Mentoring proved to be quite effective in forming a religious character on the students grade V SDIT MTA Gemolong.